2005
DOI: 10.1111/j.1365-2788.2005.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anger coping skills in individuals with intellectual disabilities

Abstract: Recent controlled studies have supported the effectiveness of anger management training for people with intellectual disabilities (IDs). This report describes an evaluation instrument designed to assess their usage of specific anger coping skills. The Profile of Anger Coping Skills (PACS) is designed for completion by a staff member or carer. Three situations are first elicited in which a client frequently displays anger. The respondent then rates each situation for the extent to which the client deploys each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(92 citation statements)
references
References 16 publications
6
84
2
Order By: Relevance
“…Table 2 shows the effect sizes obtained in these studies. All studies, bar two, reported large or very large effect sizes (mean d = 1.19); in the two studies in which only a medium-sized effect (< 0.8) was reported immediately post treatment, 11,42 the effect of the intervention subsequently increased at longer-term follow-up. Similar effect sizes were found for group (n = 10 studies; d = 1.15) and individual (n = 2 studies; d = 1.38) formats, and for self-ratings (n = 9 studies; d = 1.13) and carer ratings (n = 3 studies; d = 1.38).…”
Section: Anger In People With Intellectual Disabilitiesmentioning
confidence: 93%
See 3 more Smart Citations
“…Table 2 shows the effect sizes obtained in these studies. All studies, bar two, reported large or very large effect sizes (mean d = 1.19); in the two studies in which only a medium-sized effect (< 0.8) was reported immediately post treatment, 11,42 the effect of the intervention subsequently increased at longer-term follow-up. Similar effect sizes were found for group (n = 10 studies; d = 1.15) and individual (n = 2 studies; d = 1.38) formats, and for self-ratings (n = 9 studies; d = 1.13) and carer ratings (n = 3 studies; d = 1.38).…”
Section: Anger In People With Intellectual Disabilitiesmentioning
confidence: 93%
“…It is only recently that CBT has been adapted for people with intellectual disabilities. There is a relatively large case study literature describing successful outcomes for CBT in a variety of mental disorders, [9][10][11][12] but the evidence from controlled trials is sparse. With the exception of two small controlled trials in depression, 13,14 anger is the only psychological presentation in which controlled trials have been used to evaluate CBT interventions for people with intellectual disabilities.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional eligibility criteria were applied to exclude studies if data were included in a later study (Rose, West, & Clifford, 2000;Taylor et al, 2002), or if insufficient data were reported to perform the meta-analysis (Matson, 1981;Willner et al, 2005). Finally, the study by Silvestri (1977) was excluded because twenty-three out of thirty items of its primary outcome however, that only half the number of trials delivering individual therapy were identified compared to those delivering group therapy.…”
Section: Meta-analysesmentioning
confidence: 99%